REAKTUALISASI PANCASILA DI ERA GEN-Z - La Raessa Revita Salma; Rahma Dwi Apriliani; Rifa Nur Syaida; Ulinnuha Purwanin Tyas; Ari Metalin Ika Puspita (Civilia: Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2023)
In facing the challenges of generation Z, which tends to move away from the values ​​of nationalism and nationhood in the digital era, a Reactualization of Pancasila is needed so that the values ​​of Pancasila are maintained. In this research, the research method used is a qualitative approach with descriptive methods, focusing on behavior, challenges, impacts and efforts to instill Pancasila values ​​in generation Z. The results of the research show that generation Z tends to lack understanding and application of Pancasila in everyday life. -days due to the influence of technology and globalization. Challenges facing generation Z include individualism, dependence on technology, and decreased awareness of the values ​​of Pancasila. If Pancasila is not implemented, negative impacts could arise such as a shift in moral values ​​and potential social conflict. Efforts to instill Pancasila values ​​in generation Z involve strengthening nationalism, respect for differences, love for Indonesia, participation in democratic decisions, as well as attitudes of empathy and social justice. This research emphasizes the importance of the younger generation's awareness of the values ​​of Pancasila in maintaining unity and avoiding potential conflict in Indonesia.